Experimental investigation of the effect of hydrogen recirculation on the performance of a proton exchange membrane fuel cell. (5th January 2022) - Yu, Xingzi; Fan, Jinwei; Zhou, Yuhong; Hao, Dong; Chen, Jinrui; Yu, Tao; Zhang, Caizhi
Abstract: The hydrogen recirculation in proton exchange membrane fuel cell (PEMFC) is recommended for the hydrogen supply of PEMFC, and hydrogen ejectors are gradually being used in fuel cell vehicles due to low noise and low energy consumption. However, there is a lack of discussion about the influence of recirculation rate on the stack. Due to passive regulating mechanism of the ejectors, a miniature speed-adjustable peristaltic pump is used to simulate the hydrogen ejector in this study to investigate the effect of hydrogen recirculation on the performance of PEMFC stack. Experiments are conducted under different pump flow rates. The stack with hydrogen recirculation is proven to have better performance, but over high pump flow rate can lead to hydrogen shortage. It is interesting to find that the flow rate fluctuation of hydrogen inlet affects the stability of stack performance, and pressure drop and recovery time during purge process are proposed as effective indicators for performance analysis. Finally, pump flow rates between 60 ml/min and 105 ml/min are defined as "effective area". Based on the analysis of effective indicators, keeping at "effective area" is further proved to improve the performance of the stack, which is also useful to design hydrogen recirculation. Graphical abstract: Image 1 Highlights: The fluctuation of inlet flow rate affects the stability of stack performance. Over high pump flow rate can lead to hydrogen shortage. Pressure drop and recovery time are used as effective analysis indicators. The optimal working range of pump are determined.